ANALISIS STRUKTUR PERSAINGAN INDUSTRI JASA PENDIDIKAN TINGGI KOMPUTER UNTUK MENENTUKAN MODEL STRATEGI BERSAING - Prabowo, Harjanto; Abbas, Bahtiar Saleh; Margaret, Margaret (Industrial and Systems Engineering Assessment Journal (INASEA), 2004)
The purposes of this research is to know how high is the competition level in a computer high education service industry. Based on analysis, it can be concluded that the competition level in a computer high education service industry in Java Island is increasing in the future. But, the bargaining power in a computer high education service industry is getting weaker to the customer. Based on the competition level, the right strategy to perform is differentiate strategy focus.